PROLIFERASI KALUS DAN EMBRIOGENESIS SOMATIK JARAK PAGAR (JATROPHA CURCAS L.) DENGAN BERBAGAI KOMBINASI ZPT DAN ASAM AMINO (Callii Proliferation and Somatic Embryogenesis of Physic Nut (Jatropha curcas L.) Various Combination with PGR’s and Amino Acids) - . Lizawati (Bioplantae, 2012)
The aim of this study was to reveal a combination of plant growthregulators (PGR’s) and amino acids best callii proliferation and somaticembryogenesis physic nut. The experiment was arranged in completelyrandomized design with combination of plant growth regulators (PGR’s)and amino acids, i.e. 1 ppm TDZ + 1 ppm 2,4-D + 100 ppm glutamine;2 ppm BAP + 1 ppm 2,4 - D + 100 ppm glutamine; 1 ppm TDZ + 1 ppm2,4-D + 100 ppm CH (Casein hydrolyzate); 2 ppm BAP + 1 ppm 2,4-D+ 100 ppm CH (casein hydrolyzate); 1 ppm TDZ + 1 ppm 2,4-D; 2 ppmBAP + 1 ppm 2,4-D; Mannitol 3%; proline 5,75 ppm; proline 2.875ppm. The parameters observed were callii weight, callii diameter, calliicharacteristics (colour and structure) and the number of embryogeniccallii. The result showed that some treatment combinations of plantgrowth regulators and amino acids can increase the callii weight andcallii diameter. The color of celli was dominated by green and creamwith mostly compact structure. Meanwhile, celli friable structure as intreatment 1 ppm TDZ + 1 ppm 2,4-D; proline 5.75 ppm and 2.875 ppm.Key words : casein hydrolyzate, BAP, glutamine, proline, TDZ